2008
DOI: 10.1007/bf03345634
|View full text |Cite
|
Sign up to set email alerts
|

Protective and therapeutic effects of swimming exercise training on diabetic peripheral neuropathy of streptozotocin-induced diabetic rats

Abstract: This study suggests that swimming exercise training has protective and therapeutic effects on DPN of STZ-induced diabetic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 31 publications
4
15
0
Order By: Relevance
“…However, in the present study, a rapid increase in body weight was observed in the control groups (C-Ex1 and C-Sed); this was associated with overeating after exercise training. The slow increase in body weight shown by the 2 diabetic exercise groups was considered to be related to the body condition of the diabetic rats being improved by exercise, in agreement with the results reported by Selagzi et al (4).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, in the present study, a rapid increase in body weight was observed in the control groups (C-Ex1 and C-Sed); this was associated with overeating after exercise training. The slow increase in body weight shown by the 2 diabetic exercise groups was considered to be related to the body condition of the diabetic rats being improved by exercise, in agreement with the results reported by Selagzi et al (4).…”
Section: Discussionsupporting
confidence: 92%
“…Selagzi et al reported that swimming training for 8 weeks restored compound muscle action potential latency and prevented myelin damage (4). In the present study, it was found that starting an exercise program 8 weeks prior to the occurrence of diabetic neuropathy effec- tively prevented a decrease in the caudal NCV in diabetic rats (D-Ex1).…”
Section: Caudal Ncv (M/s) -------------------------------------------supporting
confidence: 60%
See 1 more Smart Citation
“…20,21 The importance of examining the effects of training on the right vagus nerve resides on the fact that the right vagus nerve innervates mainly the sinoatrial node which is of particular interest in regard to heart rate control during training.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with DPN who exercise regularly experience significant improvements in electrophysiological deficits and neuropathic symptoms, which is accompanied with increases in intraepidermal nerve fiber branching (Fisher et al, 2007;Hung et al, 2009;Kluding et al, 2012). In diabetic animals, exercise prevents myelin damage and attenuates changes in voltage-gated Ca 2ϩ channel function, thereby ameliorating electrophysiological deficits that occur in DPN (Selagzi et al, 2008;Shankarappa et al, 2011). In addition, exercise can increase expression of Hsp70 (Paulsen et al, 2007;Ogata et al, 2009).…”
Section: E Exercise As a Nonpharmacological Therapy For Dpnmentioning
confidence: 99%